Piękno, rozkosz, nieśmiertelność, czyli co fascynuje współczesną młodzież w powieściach o tematyce wampirycznej? - Godos, Anna (Dydaktyka Polonistyczna, 2017)
The aim of this article is to show elements which fascinate today young people in the vampirenovels. The base of the considerations are three initial components – beauty, pleasure and immortality. Each of them is supported by examples from three series of literature: Twilight by StephenieMeyer, Vampire Academy by Richelle Mead and House of Night by P. C. and Kristin Cast. The articlealso takes into consideration derivatives of each factors, as love and death. All components werediscussed in relation to youth’s emotional development by searching their own way and values tofollow them